Non-Empirical Large-Scale Search for Optical Metasurfaces - Masanobu Iwanaga (Nanomaterials, 2020)
Metasurfaces are artificially designed, on-top, thin structures on bulk substrates, realizing various functions in recent years. Most metasurfaces have been conceived of for attaining optical functions, based on elaborate human knowledge-based designs for complex structures. Here, we introduce a method for a non-empirical, large-scale structural search to find optical metasurfaces, which enable us to access intended functions without depending on human knowledge and experience. This method is different from the optimization and modification reported so far. To illustrate the outputs in the non-empirical search, we show unpredictable, optically high-performance, all-dielectric metasurfaces found in the machine search. As an extension of the finding of a higher order diffractive structure, we furthermore show a light-focusing metadevice, which is diffraction-limited and has the unique feature that the focal length is almost invariant even when the distance from the incident spot to the metadevice largely varies.